Impact of Korean Wave and Social Media on Chuseyo Coffee Business Performance - Martinus Teguh Kristianto; Gytha Nurhana Dhea Praadha Gitama; Suwandi Suwandi (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: The objective of this study is to analyze the influence of the Korean Wave on the business performance of Kopi Chuseyo and to identify the role of social media usage in enhancing business performance. Methodology/approach: This research was conducted at Kopi Chuseyo Cirebon, a café with a Korean lifestyle concept. Data were collected through an online questionnaire (Google Form) and semi-structured interviews with management to explore marketing strategies and their impact on business performance. SPSS was used for validity, reliability, and regression analysis Results/findings: The results show the Korean Wave significantly attracts young consumers to Kopi Chuseyo, while Instagram and TikTok effectively boost brand awareness, interaction, and visit frequency. Conclution: This research concludes that the Korean Wave and intensive social media use significantly improve Kopi Chuseyo’s performance by driving consumer interest, enhancing brand visibility, boosting loyalty, and strengthening its market position in the creative and culinary industries. Limitations: The study is limited by its single-location sample and reliance on consumer perceptions, which may reduce generalizability and introduce subjectivity. Contribution: This research contributes to culinary businesses' development of marketing strategies based on cultural trends and social media, and enriches studies in business management, marketing, and the creative economy.